Customizing individual heat mitigation strategies to optimize performance in elite athletes - Sekiguchi, Y.; Adams, W. M.; Hosokawa, Y.; Benjamin, C. L.; Stearns, R. L.; Huggins, R. A.; Casa, D. J. (Frontiers in Physiology, 2025)
The aim of this review is twofold: 1) provide a brief discussion surrounding the interindividual variability that has been observed within the context of heat acclimation/acclimatization, body cooling, and hydration strategies, and 2) provide the reader with a practitioner-focused approach for creating individualized heat mitigation strategies. Considering individual variability for heat acclimation and heat acclimatization, various body cooling strategies, and hydration assessment/fluid replacement is important to maximize effects of these strategies, which lead to better performance and health outcomes. There are many factors to consider, and comprehensive approaches are required. The evidenced-informed decision is critical when making an individual approach, and data will help to make decisions effectively. It is important to keep adjusting the approach based on observed data as data is useful information to check if the approach is effective. Specific considerations to individualize the plan are discussed in this review.